Changes of Altruistic Behavior and Kynurenine Pathway in Late-Life Depression - Wu, Yujie; Mai, Naikeng; Weng, Xuchu; Liang, Jiuxing; Ning, Yuping (Frontiers in Psychiatry, 2020)
Background: Depressive patients show less altruistic behavior. While, older adults present higher tendencies for altruism than younger adults. Depression and age are two of the influencing factors of altruism, kynurenine (KYN) and its metabolites. However, the characteristics of altruism in late-life depression (LLD) and its possible underlying mechanism have not been studied. Objective: We aimed to explore the characteristics of altruism in LLD patients and its neurobiological mechanism and structural brain network. We investigated whether the levels of metabolites in kynurenine pathway (KP) and white matter (WM) network topological features would influence the altruistic behavior in LLD patients. Methods: 34 LLD and 36 heathy controls (HCs) participants were included. Altruism was evaluated by the Dictator Game (DG) paradigm. Serum concentrations of KP metabolites were detected by the liquid chromatography-tandem mass spectrometry method. The topological features of the WM network were calculated from diffusion tensor imaging data in conjunction with graph-theoretical analysis. Results: The LLD participants exhibited a higher level of altruism and white matter global network properties than the HCs. KYNA/KYN ratio was associated with the DG performance and network density in the LLD group. Conclusions: KYN metabolism played an important role in altruistic behavior in LLD.